(untitled) - Tony Hopwood (London, 1992)
This book represents a new approach to skills teaching, in which integrated skills activities bring together reading, writing, listening and speaking in a natural and realistic way. It contains: Grammar practice and vocabulary building; Reading comprehension; Composition and guided writing; Listening comprehension; Self-study edition with answer key
Keywords: english language - study and teaching